Performan Ayam Ras Petelur Jantan yang Dipelihara dengan Pastured-Based System pada Kepadatan Kandang Berbeda - Zulaiha, Aulia Vivi; Dianita, Rahmi; Noperdiman, Noferdiman; Alwi, Yun (Sekolah Tinggi Pertanian Kutai Timur, 2022)
This study aims to investigate the effect of stocking density on the performance of male laying hens reared with the pastured based system. One hundred and forty seven male laying hens strain Lohman brown age 14 days old put in 21 of 1m x 1m cage according to the treatment. The treatment used was stocking density consisting of K1: 5 bird/m2, K2: 7 bird/m2, K3: 9 bird/m2. The design used in this study was a Randomized Block Design (RAK). Parameters observed in the study were ration consumption (g/head/day), final weight (g/head), feed conversion and mortality (%). The results showed that the stocking density had a significant effect (P<0.05) on consumption, final weight and feed conversion but had no significant effect (P>0.05) on the mortality rate.